Effect of Dietary Formulation Strategy, Water Source, and Water Acidification on Growth Performance and Fecal Dry Matter in Nursery Pigs - Maxwell L. Corso; Jason C. Woodworth; Mike D. Tokach; Jordan T. Gebhardt; Robert D. Goodband; Joel M. DeRouchey; Katelyn N. Gaffield; Chad W. Hastad; Alan J. Warner (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 987 weanling pigs [PIC 800 × (Fast LW × PIC L02), initially 14.9 ± 0.8 lb] were used to determine the effect of dietary formulation strategy, water source, and water acidification on growth performance and fecal dry matter (DM). Treatments were arranged in a 2 × 2 × 2 factorial with main effects of dietary formulation strategy (low ABC-4 vs conventional with ZnO), water source (rural vs well), and water acidification (with or without). Experimental diets were fed in two phases followed by a common phase 3 diet. Diets were formulated to have a dietary ABC-4 value of either 199 or 427 meq/kg in phase 1, and 249 or 441 meq/kg in phase 2. The conventional formulation strategy contained pharmacological levels of Zn from ZnO (3,026 and 2,270 ppm Zn in phase 1 and 2, respectively), whereas the low ABC-4 diet had low levels of Zn (110 ppm) provided by the trace mineral premix. Water was supplied by either rural or well sources. For the water acidification treatment, PerpHect H2O (Acid Products Company Inc., Chicago, IL) was used to acidify both water sources to a targeted pH of 4.0. Numerous 2- and 3-way interactions were observed. Overall, (d 0 to 33), a tendency for a 3-way interaction was observed for ADG (P = 0.081) where pigs fed the conventional diet with ZnO had better performance than those fed the low ABC-4 formulation strategy when provided acidified or non-acidified well water or acidified rural water. However, formulation strategy did not result in a significant change in ADG when pigs were provided with non-acidified rural water. For overall ADFI, a three-way interaction was observed (P = 0.034) where pigs fed the conventional diets with ZnO had better ADFI than those fed the low ABC-4 formulation strategy, regardless of water source or water acidification, with the greatest magnitude of improvement in pigs provided the acidified rural water. Pigs provided with rural water tended (P = 0.072) to have increased fecal DM compared to pigs provided with well water. No differences were observed for removals and mortality. Conventional diets with added ZnO resulted in increased (P < 0.05) ADG and ADFI compared to low ABC-4 diets without ZnO, which was likely due to the ZnO in the conventional diets as opposed to the ABC-4 level itself. In conclusion, formulating diets with pharmacological levels of Zn improved performance compared to low ABC-4 diet formulation strategies without added Zn, with marginal effects on performance due to water source or its acidification.
Keywords: ABC-4; growth; nursery pig; water source; zinc